THE RELATIONSHIP BETWEEN THE HEALTH, EMOTIONALITY ADJUSTMENT, AND SPORTS ABILITIES, FOR THE STUDENTS AT THE DEPARTEMENT OF EDUCATION AND SPORTS IN ALGERIA - Ababsa, Nadjibe; Mertet , Mohamed; Fedel , Kais (sports creativity, 2025)
This study aims at identifying the kind of relationship between the health adjustment, Emotionality adjustment, and sport Abilities, for the first-year students at the departments of Education and sport, Algiers, Constantine University. The sample consisted of 458 students to whom The Bell adjustment inventory Tests were administered.The general formula for correlation coefficient and the t-test were used to test the validity of the hypotheses. The study revealed the following results: 1-There were statistically significant differences between lower Quartile and Upper Quartile in health adjustment and Emotionality scale in favour of Upper Quartile. 2-There was no statistically significant correlation between health adjustment and Emotionality and sport Abilities. 3-There was no statistically significant correlation between health adjustment and sport Abilities. 4- There was no statically significant correlation between health adjustment and sport Abilities. 5-There was statistically positive